Changes in the registry of food debtors and their regulations for the issuance of Legislative Decree N° 1377 - Balarezo Reyes, Emilio José (2018)
The recent modifications that Legislative Decree No. 1377 has brought and its effect on institutions as well as on the modalities in which compliance with the food institution is sought leads us to analyze again the viability of the regulation and its respective regulations as also the way in which they have been applied in the national reality. Only with an adequate rethinking will it create the desired effect by its creators and its compliance by society and the role played by the State.